Novel Lom-dh Genes Play Potential Role in Promoting Egg Diapause of Locusta migratoria L. - Hao, Kun; Tu, Xiongbing; Ullah, Hidayat; McNeill, Mark Richard; Zhang, Zehua (Frontiers in Physiology, 2019)
Diapause hormone (DH) neuropeptides in insects are produced by the genes belonging to pban/capa family. Previous studies show that DH contains a conserved sequence of WFGPRXa that plays vital role in diapause regulation of some Lepidopteran species. However, the function of DH in other species is still unknown. In order to expand our understanding of DH function in diapause induction, Lom-pban, Lom-capa, and five candidates DH precursor genes (Lom-dh1, Lom-dh2, Lom-dh3, Lom-dh4, Lom-dh5) of Locusta migratoria L. were subsequently cloned. We identified Lom-dh1 to Lom-dh5 as novel genes that encoded five types (type I–V) of 44 tandem repeats of DH-like neuropeptides, which might promote egg diapause of L. migratoria. To test this hypothesis, we identified four types of eight new neuropeptides encoded by Lom-dh using liquid chromatography–tandem mass spectrometry from the central neuron system of L. migratoria under both short (10:14 L:D) and long (16:8 L:D) photoperiods. Later on, we synthesized four type I DH-like neuropeptides, LDH1, SDH1, LDH2, and SDH2, encoded by Lom-dh2/Lom-dh3 and injected them into fifth instar female locusts. Egg diapause incidences were observed after female oviposition. The four DH-like neuropeptides significantly increased the incidence of egg diapause under the short photoperiod, but the response was absent under the long photoperiod. Injection of dsLom-dh into female adults of L. migratoria under the short photoperiod could inhibit egg diapause, with no response under the long photoperiod. This study identified a new member of pban/capa family being the second example beside Bombyx mori, where the DH showed significant role on maternal induction of diapause.